Evaluating Functional Performance Tests in those with Non-arthritic Intra-articular Hip Pain: An International Consensus Statement - RobRoy L Martin; Amir Takla; Ashley Disantis; David Kohlrieser; Keelan Enseki; Liran Lifshitz; Louise Grant; Mario Bizzini; Mike Voight; Mark Ryan; Ryan McGovern; Timothy Tyler; et al. (North American Sports Medicine Institute, 2023)
# Background Non-arthritic intra-articular hip pain, caused by various pathologies, leads to impairments in range of motion, strength, balance, and neuromuscular control. Although functional performance tests offer valuable insights in evaluating these patients, no clear consensus exists regarding the optimal tests for this patient population. # Purpose This study aimed to establish expert consensus on the application and selection of functional performance tests in individuals presenting with non-arthritic intra-articular hip pain. # Study Design A modified Delphi technique was used with fourteen physical therapy experts, all members of the International Society for Hip Arthroscopy (ISHA). The panelists participated in three rounds of questions and related discussions to reach full consensus on the application and selection of functional performance tests. # Results The panel agreed that functional performance tests should be utilized at initial evaluation, re-evaluations, and discharge, as well as criterion for assessing readiness for returning to sports. Tests should be as part of a multimodal assessment of neuromuscular control, strength, range of motion, and balance, applied in a graded fashion depending on the patient's characteristics. Clinicians should select functional performance tests with objective scoring criteria and prioritize the use of tests with supporting psychometric evidence. A list of recommended functional performance tests with varying intensity levels is provided. Low-intensity functional performance tests encompass controlled speed in a single plane with no impact. Medium-intensity functional performance tests involve controlled speed in multiple planes with low impact. High-intensity functional performance tests include higher speeds in multiple planes with higher impact and agility requirements. Sport-specific movement tests should mimic the patient's particular activity or sport. # Conclusion This international consensus statement provides recommendations for clinicians regarding selection and utilization of functional performance tests for those with non-arthritic intra-articular hip pain. These recommendations will encourage greater consistency and standardization among clinicians during a physical therapy assessment.